The Influence of Productive Social Funds and Zakat Funds on The Development of MSMEs: Comparative Study of Social Services and BAZNAS Cilegon City - Fennty Septiani; Sulaeman Jajuli; Bani Idris Hidayanto (Mutanaqishah: Journal of Islamic Banking, 2024)
Direct Cash Assistance from the Village Fund is the term used to refer to government support that is allocated directly from the state budget. In addition to the community, they are also able to receive financial support from zakat in the form of productive assistance for micro, small, and medium enterprises (UMKM). This study employs descriptive quantitative research methods, specifically research that collects data in numerical form. The main sources of data for this research come from individuals who receive social assistance from Cilegon City Social Service and productive zakat from BAZNAS Cilegon City. Researchers collected primary data by interviewing and surveying these recipients. Providing social funds and productive zakat funds greatly impacts the growth of MSMEs. Social service and BAZNAS Cilegon City assist and manage the funds to ensure they are utilized properly for MSME development, improving the community's quality of life. The distribution of funds at BAZNAS Cilegon City is effectively done in cash for business capital, including home industries and small stalls. Currently, the distribution of social aid at DINSOS Cilegon City is not working well as the beneficiaries keep changing every year.